2022
DOI: 10.1111/1440-1630.12805
|View full text |Cite
|
Sign up to set email alerts
|

Understanding occupational therapy practice in residential aged care facilities under the Aged Care Funding Instrument: A qualitative study

Abstract: Introduction Australian occupational therapy practice in residential aged care facilities has been largely funded using the Aged Care Funding Instrument since March 2008. Literature indicates that the funding model constrains occupational therapy practice, impacting on therapists' and residents' experiences. In preparation for the implementation of the new funding model, the Australian National Aged Care Classification, it is timely to understand current practice. Therefore, the aim of this study was to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…approaches, suggesting that existing occupational therapy expertise may be underutilised to the detriment of residents. 3,24 A better understanding of the occupational therapy role in person-centred dementia residential facilities could inform ongoing development and maximise the profession's potential impact on residents.…”
Section: Practice Impactmentioning
confidence: 99%
See 3 more Smart Citations
“…approaches, suggesting that existing occupational therapy expertise may be underutilised to the detriment of residents. 3,24 A better understanding of the occupational therapy role in person-centred dementia residential facilities could inform ongoing development and maximise the profession's potential impact on residents.…”
Section: Practice Impactmentioning
confidence: 99%
“…Occupational therapists have reported challenges to implementing person‐centred dementia care in residential aged care facilities 24 . Aged care funding arrangements designed to provide more funding for residents with greater disability discourage interventions which maximise occupational opportunities for residents 24 . Australian studies by Rahja et al 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommendations for practice change and methods for practice improvement can be made based on insights gained from Key Points for Occupational Therapy • Client-centred practice remains central despite limiters of funding and time • The occupational therapy process aligns with aged care reforms • Scope of occupational therapy practice could include more preventative approaches exploring current occupational therapy practices. For example, a recent Australian study qualitatively explored occupational therapy practice in residential aged care, finding that occupational therapists were restricted by the funding model used (Calderone et al, 2022). Another older study surveyed occupational therapists about their work with children in Australia and Canada (Brown et al, 2007;Rodger et al, 2005) and found that the range of theoretical models used was largely incongruent with their chosen assessments and interventions (Rodger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%